Preface - Casalino, Gabriella; Cimitile, Marta; Ducange, Pietro; Padilla-Zea, Natalia; Pecori, Riccardo; Picerno, Pietro; Raviolo, Paolo (Communications in Computer and Information Science, 2023)
[Summary not available]
Keywords: preface; Scopus(2)